SnO2 suportado em argila para síntese de Biodiesel - Sales, Herbet Bezerra (2009)
Biodiesel production is based on the is transesterification of vegetable oils or animal fat, using homogeneous or heterogeneous catalysts. Wheres, the heterogeneous-based processing presents slower conversions compared to homogenous ones, such processes lead to noncorrosive manufacturing and avoids the occurrence of saponification reactions. Thus, this work aims at evaluating the catalytic activity of the SnO2 supported on vermiculite clay [(Mg, Fe, Al)3(Al, Si)4O10(OH)2.4H2O] for the transesterification of soybean oil. The several catalysts were obtained by impregnation of vermiculite with tin resin, previously synthesized by the polymeric precursor method. All samples were characterized thermal analysis (TG/DTA), X-ray diffraction (XRD), grazing angle XRD, X-ray fluorescence (XRF), scanning electron microscopy (SEM), infrared (IR) and confocal Raman spectroscopy is Biodiesels were synthesized using a molar ratio of 1:10 (soybean oil: ethanol), 5,0 % (wt / wt) catalys treational temperature q 65 °C, besing characterized by dynamic and kinematic viscosities. In this work the vermiculite was treated with nitric acid (HNO3). The leaching process did not modifi, the thermal stability of inorganic solids. XRF date indicates satisfactory impregnation of the catalyst supports by the precursor resins. The XRD patterns identified the presence of cassiterite phase as well as the presence of characteristic phases of clay minerals which was confirmed by grazing incidence XRD. The spectroscopic data indicated the presence of peaks characteristic of the catalytic support as well as the active phase of catalyst (SnO2). The formation of active species (alkoxide) at low temperature, on the surface of catalysts, favored the soybean oil transesterification process. Rheological studies gave preliminary evidence that the catalytic reaction occurred with reduction of 40 % in the viscosity.